Quadrant analysis of turbulence in a rectangular cavity with large aspect ratios - Guan, Dawei (2020)
By using particle image velocimetry techniques, this paper presents new insights on the turbulence structure and time-averaged flows in a rectangular cavity with large aspect ratios. The three cavity aspect ratios (L=D, where L = cavity length, D = cavity depth) used in this study are 9.9, 13.0, and 18.9. The time-averaged velocity fields and Reynolds shear stress distributions within the cavity show that the flow pattern and turbulence structures are strongly affected by the cavity aspect ratio. The quadrant dynamic analysis of velocity fluctuations on the cavity shear layers and cavity downstream edge for the three cavities is conducted. Considering all of the bursting events with hole size parameter, H = 0 in the measured planes, sweeps are found to have the highest probability of occurrence within the zone of the shear layer, and ejections dominate almost all of the areas within the cavity and a certain depth of flow immediately above the shear layer. For the highmagnitude events (H = 1), quadrant dominances are almost inverted for all of the measured planes. The quadrant shear stress distributions show that the opposing events are approximately balanced for these regions on the cavity shear layers and along the cavity downstream edge.